English Foreign Language Teachers’ Strategy in Teaching Speaking Classes: A Case Study at the Rumah Inggris Jogja - Ratri Maura Isanti; Sayit Abdul Karim; Suryo Sudiro; Gordan Matas (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2024)
This research aims to find out English teachers' strategies in teaching English-speaking classes at the Rumah English Jogja, explore the challenges faced by two English teachers in teaching speaking classes, and how they solve these problems. The present study utilized qualitative design with descriptive analysis, and the respondents were two teachers who teach English speaking classes. Observations and semi-structured interviews were employed to obtain the data. All data gathered were gone through several analysis steps: data reduction, data display, and conclusion. The findings revealed that the teaching strategies used by Mr. A were the question & answer, conversation, drilling, storytelling, and conversation strategy. Meanwhile, Mr. M, applied translation, repeating, group work, drilling, role play, reporting, game, story completion, interview, and question & answer. The result of the interview with Mr. A, and Mr M, revealed that they found it difficult to deal with new students as they were not well prepared to join the speaking class. Mr. A found it hard to stimulate and motivate his students who were not familiar with the topic discussed. Meanwhile, Mr. M, pointed out some of his difficulties, including the difference in learners' characteristics, and the variety of learners' needs, wants, and lacks in the class. Having a personal approach to students, being good friends, and creating an enjoyable learning atmosphere are several good efforts to do.